Endothelial progenitor cell number is not decreased in 34 children with Juvenile Dermatomyositis: a pilot study - Dong Xu; Akadia Kacha-Ochana; Gabrielle A. Morgan; Chiang-Ching Huang; Lauren M. Pachman (BMC, 2017)
Abstract Objective A pilot study to determine endothelial progenitor cells (EPC) number in children with Juvenile Dermatomyositis (JDM). Methods After obtaining informed consent, the EPC number from 34 fasting children with definite/probable JDM at various stages of therapy-initially untreated, active disease on medication and clinically inactive, off medication-was compared with 13 healthy fasting pediatric controls. The EPC number was determined by fluorescence activated cell sorting (FACS), CD34+/VEGFR2+/CD45dim−, and assessed in conjunction with clinical variables: disease activity scores (DAS), duration of untreated disease (DUD), TNF-α allelic polymorphism (A/G) at the promoter region of −308, number of nailfold capillary end row loop (ERL) and von Willebrand factor antigen (vWF:Ag). Correlations of the EPC numbers with the clinical and demographic variables, including DAS Skin (DAS SK), DAS Weakness (DAS WK), DAS Total Score, DUD, Cholesterol, triglycerides, High-Density Lipoprotein (HDL) and Low-Density Lipoprotein (LDL), and ERL were calculated using the Pearson correlation coefficient. Tests of associations of EPC with gender (boy vs girl), TNF-α-308A allele (GA/AA vs GG), vWF:Ag (categorized by specific ABO type) as normal/abnormal were performed, using two-sample T- tests. Results The EPC number for JDM was not significantly different from the healthy controls and was not associated with any of the clinical or cardiovascular risk factors tested. Conclusion The EPC for JDM were in the normal range, similar to adults with DM. These data support the concept that the normal EPC numbers in DM/JDM, irrespective of age, differs from adult PM, where they are decreased, perhaps reflecting a different pathophysiology.